PERILAKU NGEMPLANG DAN POLA PENYELESAIANNYA DALAM REALITAS PENGUSAHA BATIK MUSLIM KOTA PEKALONGAN - Triana Sofiani; Rita Rahmawati; Asmuni Hayat (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
Ngemplang (javanese term to call nonpayment deed of obligation) has been frightening many Batik industrialists in Pekalongan. In short, it harmed Batik industrial badly. They should get some profits for their work, just because of partner who broke the agreement by not settle his obligation, it would be gone and away. Unfortunately, the cheating practice has looked a like to be an habit in Pekalongan Batik industrials. So, I intended to study closer this phenomena and brought the facts to you. Therefore, I gathered the primary data (field research) purposively in order to show the details of Ngemplang deed in Pekalongan Batik industrials, ins and outs. I did so to the dispute resolution of it. The data were analyzed by using symbolic interactions theory and market-firm one. The result show us that ngemplang might occurred in every single chains of industry: from supplying phase, in the beginning, up to marketing one. To arrange the ngemplang dispute, the victims (owner) has performed all the way in which they can draw their credits back. Somehow, they collected the claim from ngemplang doer by hook or by crook, by using mediation; hiring some debt collectors; and/or seizing the debitorís assets/properties, activa and passiva.